(untitled) (Journal of Oriental Studies, 2018)
The composition discusses the influence of literary and artistic models to the moral and humanistic characteristics of medieval korean women. The matter of women and standpoint to the women in the world of Korea in the middle Ages was one of the most difficult questions at that time. Versatile images of women gives us an opportunity to understand the special features of korean ethnos. Through analyzing the composition “Sleep in a jade pavilion” by unknown author, we tried to depict the national concept of the confucian ideal image of woman.